Analisis Dukungan Suami Selama Kehamilan Terhadap Kunjungan Antenatal Care - Elsarika Damanik; Christina Roos Etty; Flora Sijabat; Rantauli Sibarani (Jurnal Kesehatan Komunitas, 2021)
Husband's support is a form of assistance or assistance that a husband can provide to his wife as a manifestation of his attention and affection in conducting antenatal care visits during pregnancy. This study aims to determine the relationship between husband supports for antenatal care visits at the Wanti Mabar Hilir Clinic, Medan Deli District in 2019. This study uses a cross sectional approach. Data analysis was performed using Fisher's Exact Test, found p-value (0.032), OR (5,487), CI (95%). Based on the research, it was found that the husband was less supportive (70%), 22 respondents did not regularly make antenatal care visits (73.3%). There is a relationship between husband supports for antenatal care visits. It is hoped that the husband will play an active role in providing support for mothers in making ANC visits.